2023
DOI: 10.1111/cfs.12994
|View full text |Cite
|
Sign up to set email alerts
|

The reflection of desire for revenge and revenge fantasies in drawings and narratives of sexually abused children

Abstract: Whereas the desire for revenge for an unjust deed is considered natural, its use within the therapeutic setting is scarce, specifically in sexually victimized children. The study aimed to find how experiencing sexual molestation during childhood and the revenge fantasy is reflected in drawings and narratives of sexually victimized children. Following ethical approval and signing a consent form, 14 children who experienced sexual abuse and were psychologically treated (ages 11–18) were recruited. They were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
0
0
Order By: Relevance
“…He experienced the joy of success in defeating his opponent, a sense of competence that compensated for his frustration of being bullied by powerful and assertive peers in real school life. Studies reported the empowering benefits of the desire for revenge fantasies (see Lev-Wiesel et al, 2023), such as feeling satisfaction (see Crombag et al, 2003), reducing aggression (see Gollwitzer & Denzler, 2009), enhancing victims' feelings of empowerment (see Strelan et al, 2020;Twardawski et al, 2021) and sense of justice (see Funk et al, 2014).…”
Section: Violence Can Be Depicted In Drawing and Role-play In Drawing...mentioning
confidence: 99%
“…He experienced the joy of success in defeating his opponent, a sense of competence that compensated for his frustration of being bullied by powerful and assertive peers in real school life. Studies reported the empowering benefits of the desire for revenge fantasies (see Lev-Wiesel et al, 2023), such as feeling satisfaction (see Crombag et al, 2003), reducing aggression (see Gollwitzer & Denzler, 2009), enhancing victims' feelings of empowerment (see Strelan et al, 2020;Twardawski et al, 2021) and sense of justice (see Funk et al, 2014).…”
Section: Violence Can Be Depicted In Drawing and Role-play In Drawing...mentioning
confidence: 99%